(untitled) (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
Peri‑urban agriculture offers a vital pathway to strengthen food security and urban resilience, yet systematic evaluations of land suitability in these transitional landscapes remain limited. This study integrated remote sensing and field‑based methods to characterize soils and assess their suitability for rainfed maize cultivation in the Gulum area of North‑eastern Nigeria. Cultivable land was delineated using a Random Forest classifier within Google Earth Engine, identifying 409.13 ha (about 70% of the landscape) as arable, with an overall accuracy of 91.1% (κ = 0.88) confirming the reliability of the classification. Climate parameters such as annual rainfall (1101.5 mm), dry season length (150 days), and relative humidity (43%) were derived from long‑term satellite‑based climatic records, and all were rated as highly suitable (S1). Morphological, physical, and chemical analyses of three representative pedons indicated deep, well‑drained sandy loam profiles with moderate fertility constraints. Specifically, organic carbon (0.73–1.04%), available phosphorus (10.11–12.02 mg kg-1), and cation exchange capacity (8.76–9.05 cmol kg-1) were marginal, reducing overall land ratings. Suitability classification using the parametric approach categorized all three units as moderately suitable (S2–sf), with Index of Productivity (IP) values ranging from 50.0 to 70.7, suggesting maize yield potential of 60–75% under current conditions. Under improved fertility management, all sites showed potential to attain optimal suitability (S1). These findings highlight Gulum’s strategic importance as a peri‑urban agricultural zone and emphasize the scope for boosting food security through targeted soil fertility management and the application of geospatial tools in peri‑urban planning.